Tall Morningglory (Ipomoea purpurea) Seedbank Density Effects on Pendimethalin Control Outcomes. (December 2015) - Schutte, Brian J.; Cunningham, Ashley
Abstract : Pendimethalin control failures on tall morningglory are critical shortcomings in weed-control programs for chile pepper in New Mexico. Using weed seedbank augmentation, we conducted a field study to (1) determine if pendimethalin control of tall morningglory is affected by tall morningglory seedbank density, and (2) identify weed community factors that influence labor for removing the tall morningglory plants that escape pendimethalin. The field study was complemented with a growth chamber study conducted to clarify the effects of pendimethalin rate on the putative association between tall morningglory seedbank density and pendimethalin control outcomes. Under field conditions and after square-root transformation of the dependent variable, the effects of seedbank density on seedling escape density were described with natural logarithmic functions. Although pendimethalin control of tall morningglory decreased with increasing seedbank density, seedbank additions increased labor requirements for removing tall morningglory at only a site-year characterized by low population densities in the indigenous weed community. In growth chambers, increasing pendimethalin rate negatively influenced the effects of increasing seedbank density on pendimethalin control failures. This study shows that pendimethalin control of tall morningglory is reduced when seedbank densities of this species are high. Knowledge of seedbank density effects on specific control outcomes may influence grower attitudes on management strategies that target weed seedbanks.